1995
DOI: 10.1002/jnr.490420313
|View full text |Cite
|
Sign up to set email alerts
|

Radical formation site of cerebral complex I and Parkinson's disease

Abstract: Paraquat was reduced to the paraquat radical via complex I in bovine cerebral mitochondria and accelerated lipid peroxidation. Thirty-kilodalton subunit of complex I was considered to be the radical formation site, because of its marked destruction by the paraquat radical. The lipid peroxidation by the paraquat radical was suppressed not only by superoxide dismutase (SOD) but also by mannitol. The destruction of complex I subunits via lipid peroxidation must have been caused by the hydroxyl radical which was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…Instead, enhanced dopamine synthesis in the ST, which was attributed to a possible compensatory mechanism, was observed (McCormack et al 2002). Mechanistically, the ability of paraquat to induce free radical formation (Fukushima et al 1995;Yumino et al 2002), facilitate α-synuclein fibrillation (Uversky et al 2001), and induce apoptotic cell death (Chun et al 2001) has been associated with its dopaminergic neurotoxicity.…”
Section: Exposure To Pesticides and Development Of Pdmentioning
confidence: 99%
“…Instead, enhanced dopamine synthesis in the ST, which was attributed to a possible compensatory mechanism, was observed (McCormack et al 2002). Mechanistically, the ability of paraquat to induce free radical formation (Fukushima et al 1995;Yumino et al 2002), facilitate α-synuclein fibrillation (Uversky et al 2001), and induce apoptotic cell death (Chun et al 2001) has been associated with its dopaminergic neurotoxicity.…”
Section: Exposure To Pesticides and Development Of Pdmentioning
confidence: 99%
“…These findings, and the intrinsic potential for the oxidative metabolism of dopamine to generate ROS, have suggested that oxidative stress may be involved in the death of neurons in the SNc of these patients. In addition, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, rotenone, and paraquat, compounds that can generate ROS and/or disrupt the electron transport chain, have been found to induce symptoms of PD in animal models, including, in some cases, the deposition of α-synuclein aggregates (18)(19)(20). These substances also represent environmental risk factors for PD (21).…”
mentioning
confidence: 99%
“…PD patients had higher levels of NNMT activity and protein in brain tissue than controls 17) . MNA destroyed several subunits of cerebral complex I, especially 30 kDa protein 18) , and MNA injection in rat substantia nigra pars compacta significantly decreased dopamine content in striatum 19) . Therefore, MNA is suspected as an agent causing idiopathic PD.…”
Section: Discussionmentioning
confidence: 95%